Szlachta wielkopolska na portretach trumiennych w muzeum w Międzyrzeczu: analiza genealogiczna = Międzyrzecz's museum's collection of wielkopolska's noblemen's coffin portraits: genealogical analysis - Sochala, Aneta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents the histories of noblemen families, living on the Wielkopolska-Brandenburg borderland. The histories of Bronikowscy, Bukowieccy, Dziembowscy, Kalcreuth, Prettwitz, Schlichting, Unrug and Troschke have an aura of mystery; for instance the history of the Prettwitzs' coat of arms: a Slavic warrior called Hołub reportedly played a game of chess with a black duchess, in connection with which the family's crest shows a black woman, her face dripping blood.
Keywords: Międzyrzecz (powiat); Muzeum Ziemi Międzyrzeckiej im. Alfa Kowalskiego; muzeum; portrety; portret trumienny